Theoretical insights from functional-response modeling of green sea turtle aggregation on seagrass - Naoto K. Inoue (Ecological Modelling, 2026)

First report of melon and cucumber plants as natural hosts of cowpea mild mottle virus - B. A. Silva; C. M. Kauffmann; S. B. S. Cardenas; P. S. Queiroz; A. M. V. Batista; H. B. S. Mota; A. K. Inoue-Nagata; D. M. S. Freitas; Tatsuya Nagata (Journal of Plant Pathology, 2026)

Whole Mitochondrial Genome Analysis of Killer Whales Reveals the Presence of Resident and Transient Ecotypes Around Hokkaido - Momoka Suzuki; Mami Kawai; Takashi Hayakawa; Yuki F. Kita; Yu Sato; Miho Inoue‐Murayama; Akira Shiozaki; Shin Nishida; Shimpei F. Hiruta; Hiroshi Ohizumi; Fumio Nakahara; Shigeo Saino; et al. (Marine Mammal Science, 2026)
In the North Pacific, there are at least three genetically different ecotypes of killer whales ( Orcinus orca ), referred to as resident, offshore, and transient. A previous study suggested that killer whales around Hokkaido belong to fish‐eating (resident and/or offshore ecotypes) and mammal‐eating (transient ecotype) groups. These results were supported by haplotypes based on the combination of 1193 bp of cytochrome b and 420 bp of the control region in mitochondrial genomes. However, this analysis was not sufficient to discriminate between resident and offshore ecotypes because of the short sequence lengths. In this study, we analyzed whole mitochondrial genomes of 25 killer whales sampled around Hokkaido to clarify the ecotypes and mitochondrial genome haplotypes. Phylogenetic analysis revealed the presence of resident and transient ecotypes around Hokkaido. The whales identified as residents shared an identical haplotype, which is the most common haplotype in the western North Pacific. In contrast, the transients around Hokkaido exhibited eight haplotypes, including seven novel ones among the 19 individuals, and their haplotype richness was the highest among the North Pacific populations. This result suggests that the Hokkaido coast served as a refugium for transient killer whales during the Last Glacial Maximum.

Quantification of sea turtle swimming patterns using a standardized arena to minimize effort in welfare assessment - Naoto K. Inoue (Behavioural Processes, 2025)

Modelling free residual chlorine decay in a residential district water distribution network using smart water meter data - S. Obaid; K. Hosoi; N. M. Ngoc; T. Inoue; K. Yokota (International Journal of Environmental Science and Technology, 2025)
Chlorine is the most common disinfectant in drinking water worldwide, and the free residual chlorine concentration has been stipulated at least 0.1 mg/L according to Japanese drinking water standard to ensure disinfection efficacy during distribution. In addition, Japan is also applying approximately 0.4 mg/L chlorine at treatment plants to supply tasty drinkable water to residents. Although a concentration lower than 0.4 mg/L can help avoid an unpleasant chlorine taste in the supply water, it raises challenges for maintaining residual chlorine greater than the standard throughout distribution pipelines. The chlorine concentration decreases along distribution pipes because of bulk decay and wall decay. These decays depend on the initial chlorine concentration, temperature, time, pipe material, etc. Therefore, bottle tests with the Arrhenius theory were set up on the water at the distribution inlet in the Chibata district in Kosai city, Japan at various temperatures and times to measure the bulk decay coefficient. A literature review and root square mean error matching field data were conducted to estimate the wall decay coefficient. These decay coefficients were input into EPANET 2.2 to simulate water quality using smart water meters’ hourly consumption data. Therefore, the points where chlorine concentrations were below the standard could be hourly estimated.

Human activity-associated establishment of invasive mink population estimated using environmental DNA - Toshihiro Takaba; Masayuki K. Sakata; Takashi Kanbe; Takashi Mitsuzuka; Shouko Inoue; Hiroki Mizumoto; Takahiro Nobetsu; Hitoshi Araki (Biological Invasions, 2024)

Using barcoding to reveal ecological patterns of nivicolous myxomycetes in the German Alps: How do they deal with varying snow conditions? - Maho Inoue; Jan Woyzichovski; Ángela López-Villalba; Oleg Shchepin; Anja Klahr; Yuri K. Novozhilov; Martin Schnittler (Fungal Ecology, 2024)

P19-40 Risk assessment of AFB1 due to CYP3A4-mediated biotransformation with a highly sensitive human intestinal model - L. Bai; K. Tachibana; M. Murata; T. Inoue; H. Mizuguchi; S. Maeda; K. Ikemura; M. Okuda; T. Kusakabe; M. Kondoh (Toxicology Letters, 2024)

Hybridization and reticulate evolution in Diphasiastrum (flat-branched clubmosses, Lycopodiaceae) – New data from the island of Taiwan and Vietnam - M. Schnittler; M. Inoue; O.N. Shchepin; J. Fuchs; H. Chang; P. Lamkowski; R. Knapp; K. Horn; H.W. Bennert; M. Bog (Molecular Phylogenetics and Evolution, 2024)

Estimation of survival rates of loggerhead sea turtles (Caretta caretta) in Japan using a novel framework - Naoto K. Inoue; Takashi Ishihara (Ecological Modelling, 2024)

DNA barcodes reliably differentiate between nivicolous species of Diderma (Myxomycetes, Amoebozoa) and reveal regional differences within Eurasia - Oleg N. Shchepin; Ángela López Villalba; Maho Inoue; Ilya S. Prikhodko; Daria A. Erastova; Mikhail V. Okun; Jan Woyzichovski; Yuka Yajima; Vladimir I. Gmoshinskiy; Gabriel Moreno; Yuri K. Novozhilov; Martin Schnittler (Protist, 2024)

Dominance of non-wetland-dependent pollinators in a plant community in a small natural wetland in Shimane, Japan - Tomohiro Watazu; Masayoshi K. Hiraiwa; Masahito Inoue; Hideo Mishima; Atushi Ushimaru; Tetsuro Hosaka (Journal of Plant Research, 2024)
Many wetland plants rely on insects for pollination. However, studies examining pollinator communities in wetlands remain limited. Some studies conducted in large wetlands (> 10 ha) have suggested that wetland-dependent flies, which spend their larval stage in aquatic and semi-aquatic habitats, dominate as pollinators. However, smaller wetlands surrounded by secondary forests are more prevalent in Japan, in which pollinators from the surrounding environment might be important. Additionally, information regarding floral traits that attract specific pollinator groups in wetland communities is scarce. Therefore, this study aimed to understand the characteristics of insect pollinators in a small natural wetland (2.5 ha) in Japan. We examined the major pollinator groups visiting 34 plant species and explored the relationship between the flower visitation frequency of each pollinator group and floral traits. Overall, flies were the most dominant pollinators (42%), followed by bees and wasps (33%). Cluster analysis indicated that fly-dominated plants were the most abundant among 14 of the 34 target plant species. However, 85% of the hoverflies, the most abundant flies, and 82% of the bees were non-wetland-dependent species, suggesting that these terrestrial species likely originated from the surrounding environment. Therefore, pollinators from the surrounding environment would be important in small natural wetlands. Flies tend to visit open and white/yellow flowers, whereas bees tended to visit tube-shaped flowers, as in forest and grassland ecosystems. The dominance of flies in small wetlands would be due to the dominance of flowers preferred by flies (e.g., yellow/white flowers) rather than because of their larval habitats.

Repeat-dose and embryo-fetal developmental toxicity of zinpentraxin alfa - Gautham K. Rao; Sara F. Santagostino; Lisa Wong; Ayumi Inoue; Audrey Arjomandi; Rajbharan Yadav; Wendy G. Halpern (Reproductive Toxicology, 2024)

Distribution of natural radionuclides in NORM samples from North Abu Rusheid area, Egypt - S. Sakr; K. Inoue; A. Mohamed; A.A. Ahmed; M.G. ElFeky; G.M. Saleh; M.S. Kamar; H. Arae; T. Aono; S.K. Sahoo (Journal of Environmental Radioactivity, 2023)

P25-22: Comparison of BMDL calculation performance by the recently developed Bayesian BMD calculation tools using quantal datasets of animal toxicity studies - A. Hirose; Y. Shigeta; T. Kawamura; K. Inoue; M. Matsumoto (Toxicology Letters, 2023)

P03-12: In vivo mutagenicity assessment and derivation of reference dose of styrene - Y. Murata; M. Matsumoto; T. Iso; Y. Shigeta; S. Hasegawa; T. Umano; N. Hirose; K. Horibata; K.-I. Sugiyama; K. Inoue; A. Hirose; K. Masumura (Toxicology Letters, 2023)

Distribution of brain oxytocin and vasopressin V1a receptors in chimpanzees (Pan troglodytes): comparison with humans and other primate species - Christina N. Rogers Flattery; Daniel J. Coppeto; Kiyoshi Inoue; James K. Rilling; Todd M. Preuss; Larry J. Young (Brain Structure and Function, 2022)

Nanopore sequencing of tomato mottle leaf distortion virus, a new bipartite begomovirus infecting tomato in Brazil - Thais P. Martins; Tadeu A. Souza; Patricia S. da Silva; Erich Y. T. Nakasu; Fernando L. Melo; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2021)

Area-wide insecticide resistance and endosymbiont incidence in the whitefly Bemisia tabaci MEAM1 (B biotype): A Neotropical context - R. A. C. Dângelo; M. Michereff-Filho; A. K. Inoue-Nagata; P. S. da Silva; M. Chediak; R. N. C. Guedes (Ecotoxicology, 2021)

Genetics of mouse behavioral and peripheral neural responses to sucrose - Cailu Lin; Masashi Inoue; Xia Li; Natalia P. Bosak; Yutaka Ishiwatari; Michael G. Tordoff; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

Genetic controls of Tas1r3-independent sucrose consumption in mice - Cailu Lin; Michael G. Tordoff; Xia Li; Natalia P. Bosak; Masashi Inoue; Yutaka Ishiwatari; Longhui Chen; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Complete sequence of a new bipartite begomovirus infecting Sida sp. in Northeastern Brazil - M. A. Macedo; C. M. Rêgo-Machado; M. L. Maliano; M. R. Rojas; A. K. Inoue-Nagata; R. L. Gilbertson (Archives of Virology, 2020)

Complete genome sequence of a new bipartite begomovirus infecting tomato in Brazil - Camila M. Rego-Machado; Erich Y. T. Nakasu; Rosana Blawid; Tatsuya Nagata; Alice K. Inoue-Nagata (Archives of Virology, 2019)

High-throughput sequencing reveals a novel closterovirus in arracacha (Arracacia xanthorrhiza) - Anelise F. Orílio; Rosana Blawid; Gabriela A. Costa; Suzane S. V. S. F. Gomes; Tatsuya Nagata; Nuno R. Madeira; Alice K. Inoue-Nagata; Renato O. Resende (Archives of Virology, 2018)

Sources of resistance to Potato virus Y and Pepper yellow mosaic virus in Solanum (section Lycopersicon) germplasm - Renata M. Oliveira; Érico C. Dianese; Mirtes F. Lima; Renato O. Resende; Alice K. Inoue-Nagata; Leonardo S. Boiteux (European Journal of Plant Pathology, 2018)

Characterization of tomato leaf curl purple vein virus, a new monopartite New World begomovirus infecting tomato in Northeast Brazil - M. A. Macedo; L. C. Albuquerque; M. R. Maliano; J. O. Souza; M. R. Rojas; A. K. Inoue-Nagata; R. L. Gilbertson (Archives of Virology, 2018)

Complete genome sequence of melon yellowing-associated virus from melon plants with the severe yellowing disease in Brazil - Thiago M. Costa; Rosana Blawid; Avanor C. da Costa Junior; Mirtes F. Lima; Fernando A. S. de Aragão; Genira P. de Andrade; Gilvan Pio-Ribeiro; Miguel A. Aranda; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2017)

Erratum to: Discovery of two small circular ssDNA viruses associated with the whitefly Bemisia tabaci - Erich Y. T. Nakasu; Fernando L. Melo; Miguel Michereff-Filho; Tatsuya Nagata; Bergmann M. Ribeiro; Simone G. Ribeiro; Cristiano Lacorte; Alice K. Inoue-Nagata (Archives of Virology, 2017)

Spatial variation in low-level 134Cs in the coastal sediments off central Honshu in the Sea of Japan: implications for delivery, migration, and redistribution patterns - Mutsuo Inoue; H. Uemura; H. Kofuji; K. Fujimoto; H. Takata; Y. Shirotani; N. Kudo; S. Nagao (Journal of Oceanography, 2017)

Discovery of two small circular ssDNA viruses associated with the whitefly Bemisia tabaci - Erich Y. T. Nakasu; Fernando L. Melo; Miguel Michereff-Filho; Tatsuya Nagata; Bergmann M. Ribeiro; Simone G. Ribeiro; Cristiano Lacorte; Alice K. Inoue-Nagata (Archives of Virology, 2017)

A novel vitivirus-like sequence found in Arracacia xanthorrhiza plants by high throughput sequencing - Layssa M. Oliveira; Anelise F. Orílio; Alice K. Inoue-Nagata; Tatsuya Nagata; Rosana Blawid (Archives of Virology, 2017)

Dietary fiber intake and risk of breast cancer defined by estrogen and progesterone receptor status: the Japan Public Health Center-based Prospective Study - Saki Narita; Manami Inoue; Eiko Saito; Sarah K. Abe; Norie Sawada; Junko Ishihara; Motoki Iwasaki; Taiki Yamaji; Taichi Shimazu; Shizuka Sasazuki; Kenji Shibuya; Shoichiro Tsugane (Cancer Causes & Control, 2017)

Relating food and human hair to assess mercury exposure levels in Poboya, Central Sulawesi, Indonesia - M. M. Sari; T. Inoue; Y. Matsumoto; K. Yokota (International Journal of Environmental Science and Technology, 2017)

Morphological features of an endangered Japanese strain of Cyprinus carpio : reconstruction based on seven SNP markers - K. Atsumi; H. Y. Song; H. Senou; K. Inoue; K. Mabuchi (Journal of Fish Biology, 2017)
Morphological analyses of 183 specimens of Japanese common carp Cyprinus carpio (171 from Lake Biwa and 12 from nursery ponds) using genetic hybrid indices demonstrated that the typical native Japanese strain of C. carpio has a more elongate body, more branched dorsal‐fin rays, fewer and shorter gill rakers, more developed pneumatic bulb, more coiled pneumatic duct, longer posterior swimbladder and shorter intestine than the typical introduced C. carpio . These results provide a basis for a better understanding of the ecological characteristics and taxonomic status of the endangered Japanese strain of C. carpio .

Complete genome sequence of tobacco mosqueado virus - Rosana Blawid; Kelly Barreto Rodrigues; Camila de Moraes Rêgo; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2016)

Simultaneous spawning by female stream goby Rhinogobius sp. and the association with brood cannibalism by nesting males - S. Ito; H. Iwao; J. Sakata; M. Inoue; K. Omori; Y. Yanagisawa (Journal of Fish Biology, 2016)
A laboratory experiment was conducted by varying the undersurface area of nesting substratum and the number of females in an experimental tank to elucidate the determinants of the mating pattern in the stream goby, Rhinogobius sp. cross‐band type. Males with larger nests tended to attract two or more females to their nest in a tank. Moreover, males spawned simultaneously with multiple females and entire brood cannibalism by males was rarely observed under a female‐biased sex ratio. When males spawned with a single female with low fecundity, however, entire brood cannibalism occurred at a high frequency, suggesting that a male guarding a nest with fewer eggs consumes the brood. Therefore, spawning behaviour of females that leads to a large egg mass would decrease the risk of entire brood cannibalism. In this species, simultaneous spawning by multiple females in a nest serves as a female counter‐measure against entire brood cannibalism. These results suggest that a conflict of interest between the sexes through brood cannibalism is a major determinant of simultaneous spawning.

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The importance of primary inoculum and area-wide disease management to crop health and food security - A. Bergamin Filho; A. K. Inoue-Nagata; R. B. Bassanezi; J. Belasque; L. Amorim; M. A. Macedo; J. C. Barbosa; L. Willocquet; S. Savary (Food Security, 2016)

Past climate change drives current genetic structure of an endangered freshwater mussel species - Kentaro Inoue; Brian K. Lang; David J. Berg (Molecular Ecology, 2015)
Historical‐to‐recent climate change and anthropogenic disturbance affect species distributions and genetic structure. The Rio Grande watershed of the United States and Mexico encompasses ecosystems that are intensively exploited, resulting in substantial degradation of aquatic habitats. While significant anthropogenic disturbances in the Rio Grande are recent, inhospitable conditions for freshwater organisms likely existed prior to such disturbances. A combination of anthropogenic and past climate factors may contribute to current distributions of aquatic fauna in the Rio Grande basin. We used mitochondrial DNA and 18 microsatellite loci to infer evolutionary history and genetic structure of an endangered freshwater mussel, P openaias popeii , throughout the Rio Grande drainage. We estimated spatial connectivity and gene flow across extant populations of P . popeii and used ecological niche models ( ENM s) and approximate B ayesian computation ( ABC ) to infer its evolutionary history during the Pleistocene. structure results recovered regional and local population clusters in the Rio Grande. ENM s predicted drastic reductions in suitable habitat during the last glacial maximum. ABC analyses suggested that regional population structure likely arose in this species during the mid‐to‐late Pleistocene and was followed by a late Pleistocene population bottleneck in New Mexico populations. The local population structure arose relatively recently, perhaps due to anthropogenic factors. P openaias popeii , one of the few freshwater mussel species native to the Rio Grande basin, is a case study for understanding how both geological and anthropogenic factors shape current population genetic structure. Conservation strategies for this species should account for the fragmented nature of contemporary populations.

Screening for potentially hazardous PRTR chemicals in the Lake Biwa-Yodo River basin of Japan using a one-box multimedia model - B. H. A. K. T. Ariyadasa; Akira Kondo; Yoshio Inoue (Environmental Science and Pollution Research, 2015)

Identification and characterization of 12 microsatellite loci for Physa in the Chihuahuan Desert - Kofi N. Ansah; Kentaro Inoue; Brian K. Lang; David J. Berg (Conservation Genetics Resources, 2014)

Development of 31 polymorphic microsatellite markers for guinea fowl (Numida meleagris) using next-generation sequencing technology - Princess K. Botchway; Christopher Adenyo; Boniface B. Kayang; Azusa Hayano; Miho Inoue-Murayama (Conservation Genetics Resources, 2013)

Improved loop-mediated isothermal amplification for HLA-DRB1 genotyping using RecA and a restriction enzyme for enhanced amplification specificity - Shigeki Mitsunaga; Sayoko Shimizu; Yuko Okudaira; Akira Oka; Masafumi Tanaka; Minoru Kimura; Jerzy K. Kulski; Ituro Inoue; Hidetoshi Inoko (Immunogenetics, 2013)

Development and characterization of 20 polymorphic microsatellite markers for the Texas hornshell, Popenaias popeii (Bivalvia: Unionidae), through next-generation sequencing - Kentaro Inoue; Brian K. Lang; David J. Berg (Conservation Genetics Resources, 2013)

Soybean chlorotic spot virus, a novel begomovirus infecting soybean in Brazil - Daniela Coco; Iara P. Calil; Otavio J. B. Brustolini; Anesia A. Santos; Alice K. Inoue-Nagata; Elizabeth P. B. Fontes (Archives of Virology, 2013)

Complete genome sequence of arracacha mottle virus - Anelise F. Orílio; Natalia Lucinda; André N. Dusi; Tatsuya Nagata; Alice K. Inoue-Nagata (Archives of Virology, 2013)

Further evidence reveals that okra mottle virus arose from a double recombination event - Leonardo C. Albuquerque; Silvia A. Aranha; Fernanda R. Fernandes; Alice K. Inoue-Nagata (Archives of Virology, 2013)

Complete genome sequence of pepper yellow mosaic virus, a potyvirus, occurring in Brazil - N. Lucinda; W. B. da Rocha; A. K. Inoue-Nagata; T. Nagata (Archives of Virology, 2012)

Further characterization of tomato-infecting begomoviruses in Brazil - Leonardo C. Albuquerque; Arvind Varsani; Fernanda R. Fernandes; Bruna Pinheiro; Darren P. Martin; Paulo de Tarso Oliveira Ferreira; Thaís Oliveira Lemos; Alice K. Inoue-Nagata (Archives of Virology, 2012)

Sequence determination and analysis of the NSs genes of two tospoviruses - Mariana Hallwass; Mikhail O. Leastro; Mirtes F. Lima; Alice K. Inoue-Nagata; Renato O. Resende (Archives of Virology, 2012)

The possible molecular evolution of sapoviruses by inter- and intra-genogroup recombination - Karoline dos Anjos; Lidia M. P. Lima; Paula Andreia Silva; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2011)

Molecular and biological characterization of a new Brazilian begomovirus, euphorbia yellow mosaic virus (EuYMV), infecting Euphorbia heterophylla plants - Fernanda R. Fernandes; Leonardo C. Albuquerque; Cristiane L. de Oliveira; Andréa R. R. Cruz; Wesley B. da Rocha; Talita G. Pereira; Fernanda Y. B. Naito; Natália de M. Dias; Tatsuya Nagata; Josias C. Faria; Francisco M. Zerbini; Francisco J. L. Aragão; et al. (Archives of Virology, 2011)

Search in Solanum (section Lycopersicon) germplasm for sources of broad-spectrum resistance to four Tospovirus species - É. C. Dianese; M. E. N. Fonseca; A. K. Inoue-Nagata; R. O. Resende; L. S. Boiteux (Euphytica, 2011)

A novel monopartite begomovirus infecting sweet potato in Brazil - Leonardo C. Albuquerque; Alice K. Inoue-Nagata; Bruna Pinheiro; Simone da G. Ribeiro; Renato O. Resende; Enrique Moriones; Jesús Navas-Castillo (Archives of Virology, 2011)

Potential for spectral indices to remotely sense phosphorus and potassium content of legume-based pasture as a means of assessing soil phosphorus and potassium fertility status - K. Kawamura; A. D. Mackay; M. P. Tuohy; K. Betteridge; I. D. Sanches; Y. Inoue (International Journal of Remote Sensing, 2011)

Seasonal Changes of PFOS and PFOA Concentrations in Lake Biwa Water - T. Tsuda; A. Inoue; T. Igawa; K. Tanaka (Bulletin of Environmental Contamination and Toxicology, 2010)

Temozolomide Delivery to Tumor Cells by a Multifunctional Nano Vehicle Based on Poly(β-L-malic acid) - Rameshwar Patil; José Portilla-Arias; Hui Ding; Satoshi Inoue; Bindu Konda; Jinwei Hu; Kolja A. Wawrowsky; Paul K. Shin; Keith L. Black; Eggehard Holler; Julia Y. Ljubimova (Pharmaceutical Research, 2010)

Complete genome sequence of Brugmansia suaveolens mottle virus, a potyvirus from an ornamental shrub - Natalia Lucinda; Alice K. Inoue-Nagata; Elliot W. Kitajima; Tatsuya Nagata (Archives of Virology, 2010)

Analysis of the triple gene block sequence in an important melon pathogen, Melon yellowing-associated virus - Tatsuya Nagata; Luisa S. Dutra; Priscila A. Oliveira; Antonio C. de Ávila; Alice K. Inoue-Nagata (Journal of General Plant Pathology, 2010)

Colony growth and reproductive ability of feral nests of the introduced bumblebee Bombus terrestris in northern Japan - M. N. Inoue; J. Yokoyama; K. Tsuchida (Insectes Sociaux, 2010)

Characterization of tomato yellow vein streak virus, a begomovirus from Brazil - L. C. Albuquerque; D. P. Martin; A. C. Ávila; A. K. Inoue-Nagata (Virus Genes, 2010)

Natural infection of Nicandra physaloides by Tomato severe rugose virus in Brazil - Julio C. Barbosa; Sarah S. Barreto; Alice K. Inoue-Nagata; Marcelo S. Reis; Ana Carolina Firmino; Armando Bergamin Filho; Jorge Alberto Marques Rezende (Journal of General Plant Pathology, 2009)

Pesticides in Water and Sediment from Littoral Area of Lake Biwa - T. Tsuda; T. Nakamura; A. Inoue; K. Tanaka (Bulletin of Environmental Contamination and Toxicology, 2009)

Pesticides in Water, Fish and Shellfish from Littoral Area of Lake Biwa - T. Tsuda; T. Nakamura; A. Inoue; K. Tanaka (Bulletin of Environmental Contamination and Toxicology, 2009)

Brugmansia suaveolens mottle virus, a novel potyvirus causing leaf mottling of Brugmansia suaveolens in Brazil - N. Lucinda; T. Nagata; A. K. Inoue-Nagata; R. B. Salaroli; E. W. Kitajima (Archives of Virology, 2008)

Changes in blood flow in conduit artery and veins of the upper arm during leg exercise in humans - Anna Ooue; Tomoko K. Ichinose; Yoshimitsu Inoue; Takeshi Nishiyasu; Shunsaku Koga; Narihiko Kondo (European Journal of Applied Physiology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Reflectance characteristics of major land surfaces in slash‐and‐burn ecosystems in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2008)

Deoxymugineic acid increases Zn translocation in Zn-deficient rice plants - Motofumi Suzuki; Takashi Tsukamoto; Haruhiko Inoue; Satoshi Watanabe; Shinpei Matsuhashi; Michiko Takahashi; Hiromi Nakanishi; Satoshi Mori; Naoko K. Nishizawa (Plant Molecular Biology, 2008)

Identification and localisation of the rice nicotianamine aminotransferase gene OsNAAT1 expression suggests the site of phytosiderophore synthesis in rice - Haruhiko Inoue; Michiko Takahashi; Takanori Kobayashi; Motofumi Suzuki; Hiromi Nakanishi; Satoshi Mori; Naoko K. Nishizawa (Plant Molecular Biology, 2008)

Traceability of slash‐and‐burn land‐use history using optical satellite sensor imagery: a basis for chronosequential assessment of ecosystem carbon stock in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2007)

Natural infection of Alternanthera tenella (Amaranthaceae) by a new potyvirus - A. M. R. Almeida; C. Y. Fukushigue; F. Sartori; E. Binneck; S. R. R. Marin; A. K. Inoue-nagata; C. M. Chagas; E. R. Souto; T. Mituti (Archives of Virology, 2007)

Identification and characterization of RNA-dependent RNA polymerase activity in recombinant Japanese encephalitis virus NS5 protein - F. Yu; F. Hasebe; S. Inoue; E. G. M. Mathenge; K. Morita (Archives of Virology, 2007)

Changes in blood flow in a conduit artery and superficial vein of the upper arm during passive heating in humans - Anna Ooue; Tomoko Ichinose-Kuwahara; A. K. M. Shamsuddin; Yoshimitsu Inoue; Takeshi Nishiyasu; Shunsaku Koga; Narihiko Kondo (European Journal of Applied Physiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of naphthoquinone on airway responsiveness in the presence or absence of antigen in mice - Ken-ichiro Inoue; Hirohisa Takano; Takamichi Ichinose; Shigeo Tomura; Rie Yanagisawa; Miho Sakurai; Daigo Sumi; Arthur K. Cho; Kyoko Hiyoshi; Yoshito Kumagai (Archives of Toxicology, 2007)

The expression of iron homeostasis-related genes during rice germination - Tomoko Nozoye; Haruhiko Inoue; Michiko Takahashi; Yasuhiro Ishimaru; Hiromi Nakanishi; Satoshi Mori; Naoko K. Nishizawa (Plant Molecular Biology, 2007)

Cospeciation in the triplex symbiosis of termite gut protists ( Pseudotrichonympha spp.), their hosts, and their bacterial endosymbionts - S. NODA; O. KITADE; T. INOUE; M. KAWAI; M. KANUKA; K. HIROSHIMA; Y. HONGOH; R. CONSTANTINO; V. UYS; J. ZHONG; T. KUDO; M. OHKUMA (Molecular Ecology, 2007)
A number of cophylogenetic relationships between two organisms namely a host and a symbiont or parasite have been studied to date; however, organismal interactions in nature usually involve multiple members. Here, we investigated the cospeciation of a triplex symbiotic system comprising a hierarchy of three organisms — termites of the family Rhinotermitidae, cellulolytic protists of the genus Pseudotrichonympha in the guts of these termites, and intracellular bacterial symbionts of the protists. The molecular phylogeny was inferred based on two mitochondrial genes for the termites and nuclear small‐subunit rRNA genes for the protists and their endosymbionts, and these were compared. Although intestinal microorganisms are generally considered to have looser associations with the host than intracellular symbionts, the Pseudotrichonympha protists showed almost complete codivergence with the host termites, probably due to strict transmissions by proctodeal trophallaxis or coprophagy based on the social behaviour of the termites. Except for one case, the endosymbiotic bacteria of the protists formed a monophyletic lineage in the order Bacteroidales, and the branching pattern was almost identical to those of the protists and the termites. However, some non‐codivergent evolutionary events were evident. The members of this triplex symbiotic system appear to have cospeciated during their evolution with minor exceptions; the evolutionary relationships were probably established by termite sociality and the complex microbial community in the gut.

Fluctuating serotonergic function in premenstrual dysphoric disorder and premenstrual syndrome: findings from neuroendocrine challenge tests - Y. Inoue; T. Terao; N. Iwata; K. Okamoto; H. Kojima; T. Okamoto; R. Yoshimura; J. Nakamura (Psychopharmacology, 2006)

Development of Stable Isotope Dilution Quantification Liquid Chromatography–Mass Spectrometry Method for Estimation of Exposure Levels of Bisphenol A, 4-tert-Octylphenol, 4-Nonylphenol, Tetrabromobisphenol A, and Pentachlorophenol in Indoor Air - K. Inoue; S. Yoshida; S. Nakayama; R. Ito; N. Okanouchi; H. Nakazawa (Archives of Environmental Contamination and Toxicology, 2006)

The Monitoring of Insects to Maintain Biodiversity in Ogawa Fores Reserve - S. Makino; H. Goto; T. Inoue; M. Sueyoshi; K. Okabe; M. Hasegawa; K. Hamaguchi; H. Ctanaka; I. Okochi (Environmental Monitoring and Assessment, 2006)

Expression of foreign type I ribulose-1,5-bisphosphate carboxylase/ oxygenase (EC 4.1.1.39) stimulates photosynthesis in cyanobacterium Synechococcus PCC7942 cells - T. Iwaki; K. Haranoh; N. Inoue; K. Kojima; R. Satoh; T. Nishino; S. Wada; H. Ihara; S. Tsuyama; H. Kobayashi; A. Wadano (Photosynthesis Research, 2006)

The phase boundary between wadsleyite and ringwoodite in Mg2SiO4 determined by in situ X-ray diffraction - T. Inoue; T. Irifune; Y. Higo; T. Sanehira; Y. Sueda; A. Yamada; T. Shinmei; D. Yamazaki; J. Ando; K. Funakoshi; W. Utsumi (Physics and Chemistry of Minerals, 2006)

Assessment of room temperature influence on finger blood flow response induced by short-term grasping of vibrating handle - M. H. Mahbub; M. Inoue; K. Yokoyama; M. S. Laskar; H. Ohnari; K. Suizu; J. Inagaki; Y. Takahashi; N. Harada (International Archives of Occupational and Environmental Health, 2006)

Pharmacokinetics and pharmacodynamics of etizolam are influenced by polymorphic CYP2C19 activity - T. Fukasawa; N. Yasui–Furukori; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

High-temperature and high-pressure equation of state for the hexagonal phase in the system NaAlSiO4 – MgAl2O4 - T. Shinmei; T. Sanehira; D. Yamazaki; T. Inoue; T. Irifune; K. Funakoshi; A. Nozawa (Physics and Chemistry of Minerals, 2005)

Effect of room temperature on percentage finger systolic blood pressure response to finger cooling - M. S. Laskar; K. Ohmura; M. Inoue; K. Yokoyama; J. Inagaki; Y. Takahashi; M. H. Mahbub; H. Ohnari; N. Harada (European Journal of Applied Physiology, 2005)

Effect of skin temperature on the ion reabsorption capacity of sweat glands during exercise in humans - A. K. M. Shamsuddin; T. Kuwahara; A. Oue; C. Nomura; S. Koga; Y. Inoue; N. Kondo (European Journal of Applied Physiology, 2005)

Roles of Volume-sensitive Cl− Channel in Cisplatin-induced Apoptosis in Human Epidermoid Cancer Cells - T. Ise; T. Shimizu; E.L. Lee; H. Inoue; K. Kohno; Y. Okada (The Journal of Membrane Biology, 2005)

Induction of the metabolism of etizolam by carbamazepine in humans - S. Kondo; T. Fukasawa; N. Yasui-Furukori; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

A novel melon flexivirus transmitted by whitefly - T. Nagata; D. M. T. Alves; A. K. Inoue-Nagata; T.-Y. Tian; E. W. Kitajima; J. E. Cardoso; A. C. de vila (Archives of Virology, 2005)

Changes in Activities of Enzymes Related to Energy Metabolism in Peripheral Leukocytes of Fattening Steers - N. Kimura; I. Yoshimura; T. Sako; A. Inoue; K. Tadami; T. Arai (Veterinary Research Communications, 2005)

Inhibition of the metabolism of etizolam by itraconazole in humans: evidence for the involvement of CYP3A4 in etizolam metabolism - K. Araki; N. Yasui-Furukori; T. Fukasawa; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2004)

Characterization of Oita virus 296/1972 of Rhabdoviridae isolated from a horseshoe bat bearing characteristics of both lyssavirus and vesiculovirus - K. Tanaka; Y. Sato; S. Morikawa; D. Hayasaka; M. Moriyama; T. Ono; A. Yamada; T. Kurata; T. Iwasaki; S. Inoue; S. Kanai (Archives of Virology, 2004)

Development and implementation of a database system to manage a large-scale mouse ENU-mutagenesis program - Hiroshi Masuya; Yuji Nakai; Hiromi Motegi; Norio Niinaya; Yuichiro Kida; Yoshiharu Kaneko; Haruhiko Aritake; Nobuaki Suzuki; Jun Ishii; Koji Koorikawa; Tomohiro Suzuki; Maki Inoue; et al. (Mammalian Genome, 2004)

Augmented cytoplasmic Smad4 induces acceleration of TGF-?1 signaling in renal tubulointerstitial cells of hereditary nephrotic ICGN mice with chronic renal fibrosis; possible role for myofibroblastic differentiation - Y. Goto; N. Manabe; K. Uchio-Yamada; M. Yamaguchi-Yamada; N. Inoue; Y. Yamamoto; A. Ogura; N. Nagano; H. Miyamoto (Cell and Tissue Research, 2004)

Character displacement in style length between pollinator-sharing Clerodendrum trichotomum and C. izuinsulare (Verbenaceae) - T. Miyake; K. Inoue (Plant Systematics and Evolution, 2003)

Perfluorooctane Sulfonate Contamination of Drinking Water in the Tama River, Japan: Estimated Effects on Resident Serum Levels - K. Harada; N. Saito; K. Sasaki; K. Inoue; A. Koizumi (Bulletin of Environmental Contamination and Toxicology, 2003)

Involvement of microtubules in rhizoid differentiation of Spirogyra species - K. Yoshida; N. Inoue; S. Sonobe; T. Shimmen (Protoplasma, 2003)

The effects of histamine on the lipopolysaccharide-induced metallothionein-I mRNA expression in the mouse spleen - T. Inoue; M. Nakano; N. Oda; T. Yoneyama; Y. Okano; K. Onodera; H. Furuta; C. A. Sogawa; N. Sogawa (Inflammation Research, 2003)

In situ X-ray observations of phase transitions in MgAl 2 O 4 spinel to 40 GPa using multianvil apparatus with sintered diamond anvils - T. Irifune; H. Naka; T. Sanehira; T. Inoue; K. Funakoshi (Physics and Chemistry of Minerals, 2002)

Pepper yellow mosaic virus, a new potyvirus in sweetpepper, Capsicum annuum - A. K. Inoue-Nagata; M. E. N. Fonseca; R. O. Resende; L. S. Boiteux; D. C. Monte; A. N. Dusi; A. C. de ávila; R. A. A. van der Vlugt (Archives of Virology, 2002)

Complete nucleotide sequence of the genomic RNA of Aconitum latent virus (genus Carlavirus) isolated from Delphinium sp. - S. Fuji; H. Yamamoto; M. Inoue; K. Yamashita; Y. Fukui; H. Furuya; H. Naito (Archives of Virology, 2002)

Effect of MS-153 on the development of behavioral sensitization to locomotion- and ataxia-inducing effects of phencyclidine - Abekawa T.; Honda M.; Ito K.; Inoue T.; Koyama T. (Psychopharmacology, 2002)

Genetic identification of two distinct DNA polymerases, DnaE and PolC, that are essential for chromosomal DNA replication in Staphylococcus aureus - R. Inoue; C. Kaito; M. Tanabe; K. Kamura; N. Akimitsu; K. Sekimizu (Molecular Genetics and Genomics, 2001)

Evaluation of formation potential of trihalomethanes and mutagens due to chlorination of river water along the Kizu River in the Yodo River system in Japan - S. Sanukida; T. Nobukawa; M. Ichihara; H. Shima; K. Inoue; S. Nakachi (Limnology, 2001)

Karyotype analysis of Nicotiana kawakamii Y. Ohashi using DAPI banding and rDNA FISH - R. Nakamura; S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2001)

Ecological Evaluation of Gadolinium Toxicity Compared with Other Heavy Metals Using an Aquatic Microcosm - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2001)

High-resolution genetic mapping of the saccharin preference locus (Sac) and the putative sweet taste receptor (T1R1) gene (Gpr70) to mouse distal Chromosome 4 - Xia Li; Masashi Inoue; Danielle R. Reed; Taufiqul Huque; Ralph B. Puchalski; Michael G. Tordoff; Yuzo Ninomiya; Gary K. Beauchamp; Alexander A. Bachmanov (Mammalian Genome, 2001)

Quantitative chromosome maps and rDNA localization in the T subgenome of Nicotiana tabacum L. and its putative progenitors - S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2000)

Enterobacter cowaniisp. nov., a New Species of the Family Enterobacteriaceae - Kohaku Inoue; K. Sugiyama; Y. Kosako; R. Sakazaki; S. Yamai (Current Microbiology, 2000)

Simple Aquatic Microcosm for Ecotoxicity Screening at the Community Level - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2000)

Determination of the phase boundary between ilmenite and perovskite in MgSiO 3 by in situ X-ray diffraction and quench experiments - K. Kuroda; T. Irifune; T. Inoue; N. Nishiyama; M. Miyashita; K. Funakoshi; W. Utsumi (Physics and Chemistry of Minerals, 2000)

Subsite-specific risk factors for hypopharyngeal and esophageal cancer (Japan) - T. Takezaki; M. Shinoda; S. Hatooka; Y. Hasegawa; S. Nakamura; K. Hirose; M. Inoue; N. Hamajima; T. Kuroishi; H. Matsuura; K. Tajima (Cancer Causes & Control, 2000)

Role of the pretectal nucleus of the optic tract in short-latency ocular following responses in monkeys - Y. Inoue; A. Takemura; M.J. Mustari; K. Kawano (Experimental Brain Research, 2000)

Physiological significance of hyperpolarization-activated inward currents (I h) in smooth muscle cells from the circular layers of pregnant rat myometrium - K. Okabe; Y. Inoue; T. Kawarabayashi; H. Kajiya; F. Okamoto; H. Soeda (Pflügers Archiv - European Journal of Physiology, 1999)

Physiological significance of hyperpolarization-activated inward currents ( I h ) in smooth muscle cells from the circular layers of pregnant rat myometrium - K. Okabe; Y. Inoue; T. Kawarabayashi; H. Kajiya; F. Okamoto; H. Soeda (Pflügers Archiv - European Journal of Physiology, 1999)

Effects of N-nitrosodimethylamine (NDMA) on the oxidative status of rat liver - M. Taniguchi; A. Yasutake; K. Takedomi; K. Inoue (Archives of Toxicology, 1999)

PCR-based method for identifying the S-genotypes of Japanese pear cultivars - T. Ishimizu; K. Inoue; M. Shimonaka; T. Saito; O. Terai; S. Norioka (Theoretical and Applied Genetics, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Oculomotor sequence learning: a positron emission tomography study - R. Kawashima; J. Tanji; K. Okada; Motoaki Sugiura; Kazunori Sato; Shigeo Kinomura; Kentaro Inoue; Akira Ogawa; Hiroshi Fukuda (Experimental Brain Research, 1998)

Dependence of short-latency ocular following and associated activity in the medial superior temporal area (MST) on ocular vergence - Y. Inoue; A. Takemura; K. Kawano; T. Kitama; F. A. Miles (Experimental Brain Research, 1998)

Reduced glutathione promotes callus growth and shoot development in a shoot tip culture of apple root stock M26 - K. Nomura; S. Matsumoto; K. Masuda; M. Inoue (Plant Cell Reports, 1998)

Tea and coffee consumption and the risk of digestive tract cancers: data from a comparative case-referent study in Japan - M. Inoue; K. Tajima; K. Hirose; N. Hamajima; T. Takezaki; T. Kuroishi; S. Tominaga (Cancer Causes & Control, 1998)

Effects of various factors including the CYP2D6 genotype and coadministration of flunitrazepam on the steady-state plasma concentrations of bromperidol and its reduced metabolite - A. Suzuki; K. Otani; K. Mihara; N. Yasui; T. Kondo; N. Tokinaga; H. Furukori; S. Kaneko; Y. Inoue; K. Hayashi (Psychopharmacology, 1998)

The Urinary Excretion of Arsenic Metabolites After a Single Oral Administration of Dimethylarsinic Acid to Rats - K. Yoshida; H. Chen; Y. Inoue; H. Wanibuchi; S. Fukushima; K. Kuroda; G. Endo (Archives of Environmental Contamination and Toxicology, 1997)

Pyruvate alleviates toxic effects of ethanol on cells in culture - K. Fukaya; M. Miyazaki; H. Pu; B. Katayama; Y. Inoue; R. Ohashi; C. Nakamura; M. Namba (Archives of Toxicology, 1997)

Sucrose consumption in mice: Major influence of two genetic Loci affecting peripheral sensory responses - Alexander A. Bachmanov; Danielle R. Reed; Yuro Ninomiya; Masashi Inoue; Michael G. Tordoff; R. Arlen Price; Gary K. Beauchamp (Mammalian Genome, 1997)

Prolactin-like immunoreactivity in the granules of neural complex cells in the ascidian Halocynthia roretzi - M. Ogawa; K. Inoue; S. Kikuyama; K. Terakado; K. Yamamoto (Cell and Tissue Research, 1997)

Interaction between carbamazepine and bromperidol - K. Otani; M. Ishida; N. Yasui; T. Kondo; K. Mihara; A. Suzuki; H. Furukori; S. Kaneko; Y. Inoue (European Journal of Clinical Pharmacology, 1997)

A possible hybrid zone in the Mytilus edulis complex in Japan revealed by PCR markers - K. Inoue; S. Odo; T. Noda; S. Nakao; S. Takeyama; E. Yamaha; F. Yamazaki; S. Harayama (Marine Biology, 1997)

Monoclonal antibodies against glutaraldehyde-conjugated histamine: application to immunocytochemistry - K. Fujiwara; Tsunehiro Kitagawa; Yasuhisa Inoue; Gerard Alonso (Histochemistry and Cell Biology, 1997)

Molecular cloning, sequencing, and expression inEscherichia coli of the potato virus Y cytoplasmic inclusion gene - K. Ohshima; A. K. Inoue; E. Shikata (Archives of Virology, 1993)

Replication of rat coronavirus in a rat cell line, LBC - N. Hirano; K. Ono; Y. Sada; A. Inoue; T. Murakami; H. Takamaru (Archives of Virology, 1985)

Morphology of SMON virus - Hiroko Bessho; Yoko Nishibe; Y. K. Inoue (Archives of Virology, 1974)

Relationship between SMON virus and avian infectious laryngotracheitis virus - Yoko Nishibe; Y. K. Inoue (Archives of Virology, 1974)

Properties of virus associated with subacute myelo-optico-neuropathy - Yoko Nishibe; T. Kimura; Y. K. Inoue (Archives of Virology, 1973)

Clonal analysis of tumorigenesis of bovine adenovirus type 3 and isolation of a nontumorigenic variant - Y. Nishibe; T. Kimura; Y. K. Inoue (Archives of Virology, 1970)